Insentif fiskal berupa kemudahan impor tujuan ekspor dan kinerja ekspor IKM di Indonesia - Adriyanto, F.X. Dewo Kusumo; Qibthiyyah, Riatu Mariatul (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research aims to analyze the benefits of fiscal incentives provided through KITE IKM facilities on the export performance of SMEs in Indonesia. To achieve this goal, this study used a Fixed Effect Model with the object of research is SME users of KITE IKM facilities which was grouped into 14 business fields during the first quarter of 2014 to the fourth quarter of 2020. To explain export performance, three variables are used, namely export value, export volume and export concentration. The results show that the fiscal incentives provided through the KITE IKM facility are positively and significantly correlated to the export performance of SMEs in Indonesia.